Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Tenaga Kerja dengan Motivasi Kerja Sebagai Variabel Intervening - Akhmad Prihartono; Aty Herawati (Syntax Idea)
This research aims to investigate the influence of leadership style and work discipline on employee performance with work motivation as an intervening variable. The study was conducted at PT. Pesona Taman Indo. The sample size used consisted of 39 employees, selected using purposive sampling method, representing the entire population of 73 employees. Data were collected through the distribution of questionnaires. The analytical techniques used were descriptive analysis and Partial Least Squares (PLS) analysis. The research results indicate that leadership style has an influence on work motivation, work discipline has an influence on work motivation, leadership style has an influence on employee performance, work discipline does not have an influence on employee performance, and work motivation does not have an influence on employee performance. In the future, it is recommended that for leadership style, when some employees disagree with the leader's good behavior, leaders should strive to exhibit good behavior towards their employees. In terms of work discipline, there are some employees who do not adhere to the dress code, and this should be addressed to ensure uniformity. Regarding work motivation, some employees may become bored with repetitive tasks, so introducing new innovations may help keep employees engaged. Lastly, for employee performance, training may be necessary for those who are unable to complete their tasks effectively.